2021
DOI: 10.1038/s41467-020-20726-8
|View full text |Cite
|
Sign up to set email alerts
|

Contact-independent killing mediated by a T6SS effector with intrinsic cell-entry properties

Abstract: Bacterial type VI secretion systems (T6SSs) inject toxic effectors into adjacent eukaryotic and prokaryotic cells. It is generally thought that this process requires physical contact between the two cells. Here, we provide evidence of contact-independent killing by a T6SS-secreted effector. We show that the pathogen Yersinia pseudotuberculosis uses a T6SS (T6SS-3) to secrete a nuclease effector that kills other bacteria in vitro and facilitates gut colonization in mice. The effector (Tce1) is a small protein t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 51 publications
1
57
0
Order By: Relevance
“…To the best of our knowledge, this study is the first to report the role of T6SS in bacterial competition through the use of OMVs. It further supports the idea that T6SS gives bacteria a competitive advantage and acts as evolutionary factors that shape the composition of the microbial community [43,[66][67][68].…”
Section: Discussionsupporting
confidence: 77%
“…To the best of our knowledge, this study is the first to report the role of T6SS in bacterial competition through the use of OMVs. It further supports the idea that T6SS gives bacteria a competitive advantage and acts as evolutionary factors that shape the composition of the microbial community [43,[66][67][68].…”
Section: Discussionsupporting
confidence: 77%
“…Optical density (OD 600 ) of the bacterial cultures was measured at 2-h time intervals and growth curve was plotted (time interval on x-axis and OD 600 on y-axis). DAPI staining and microscopic analysis 4 0 ,6-diamidino-2-phenylindole (DAPI) staining and microscopic analysis were performed to visualize cell death and nuclear degradation in the recombinant E. coli cells, as described previously (Pissaridou et al, 2018;Song et al, 2021). Briefly, 10 ml of recombinant E. coli (BL21) cells were grown in LB media containing appropriate antibiotics.…”
Section: Bacterial Growth Curvementioning
confidence: 99%
“…Traditionally, T6SS is recognized as a contact-dependent molecular machinery. Recent studies revealed that T6SSs play crucial roles in shaping the composition of a microbial population in hosts or environmental niches, either by directly killing competing cells via contactdependent (Russell et al, 2011) and contact-independent (Song et al, 2021) translocation of toxins, or by competing for essential nutrients via contact-independent secretion of metal ion binding effectors. For example, the T6SS-HmuR-mediated active zinc transport system is involved in a contact-independent bacteriabacteria competition for nutrients (Si et al, 2017a,b;Han et al, 2019;Wang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the T6SS function is determined by the loading effectors that can be delivered extracellularly based on energy consumption and load transport (Cianfanelli et al, 2016;Coulthurst, 2019). Many T6SS effectors related to virulence or competition that target the cell wall, membranes, and nucleic acids have been reported (Yang et al, 2018;Song et al, 2021). Several effectors with special activities have also been found.…”
Section: Introductionmentioning
confidence: 99%